Analisis Penanganan Longsoran Pada Bangunan Pelimpah Bendungan Ciawi - Nur Alvi Anisa; Ignatius Sriyana; Suseno Darsono (Universitas Islam 45, 2023)
The shallow landslide on the left slope of the Ciawi Dam spillway occurred in June 2020. The landslide occurred gradually and disrupted the progress of the dam construction. Therefore, this study aims to analyze the stability of the slope and determine the safe number of the slope then providing recommendations for proper handling. The method used in this study is the limit equilibrium method with the SLOPE/W geostudio program which is run in two methods of determining safety factor, Bishop and Fellenius/Ordinary. Based on the results of the stability analysis, the safety factor is 0.915 for Bishop method and 0.852 for Ordinary method. The first attempt at handling the slopes was to reduce the slope, but this effort did not provide a significant increase in the number of safety factor. The next handling is to use the reinforcement of 3 borepiles with a depth of 35 m, 40 m, and 45 m with a distance between the piles of 40 mm with a shear strength of 150 kN. This effort provides a safety factor number of 1.754 Bishop's method and 1.546 Ordinary’s method with the result that it meets the safety requirements of slope reinforcement.